Serum vimentin predicts mortality in pediatric severe sepsis: A prospective observational study. (August 2022) - Miao, Huijie; Cui, Yun; Lu, Ye; Sun, Ting; Dou, Jiaying; Ren, Yuqian; Wang, Chunxia; Zhang, Yucai
Abstract: Objectives: Vascular hyperpermeability by loss of endothelial barrier integrity is a hallmark of sepsis. Vimentin is involved in the regulation of the endothelial function and inflammatory response. However, the serum level of vimentin and its clinical relevance in pediatric severe sepsis (PSS) remain unknown. Methods: We conducted a prospective study of PSS cases who were admitted to the pediatric intensive care unit (PICU) from January 2018 to December 2020. Results: A total of 108 patients with PSS with a median age of 19.5 month were enrolled. The hospital mortality rate was 19.44% (21/108). Comparing with healthy controls, serum vimentin levels on PICU admission were significantly higher in patients with PSS ( P < 0.001). The area under the ROC curve for vimentin to predict the hospital mortality was 0.712 (95% CI: 0.578–846) with a sensitivity of 71.43% and a specificity of 70.11%. Moreover, hospital mortality was significantly higher in patients with vimentin level over the cutoff value of 24.53 ng/ml than in patients with vimentin level below 24.53 ng/ml ( P < 0.001). Conclusions: Serum vimentin level as an indicator of endothelial injury is associated with the prognosis of PSS, and serum vimentin level ≥24.53 ng/ml on PICU admission predicts high risk for hospital mortality in PSS.